2020
DOI: 10.33448/rsd-v9i4.2887
|View full text |Cite
|
Sign up to set email alerts
|

Drying kinetics and effective diffusion of watermelon seeds

Abstract: ResumoAs sementes de melancia (Citrullus lanatus) apresentam elevado teor de água, e necessitam passar pelo processo de secagem para assegurar o armazenamento e manter a viabilidade da Research, Society and Development, v. 9, n. 4, e16972887, 2020 (CC BY 4.0) | ISSN 2525-3409 | DOI: http://dx.doi.org/10.33448/rsd-v9i4.2887 2 semente. Neste cenário, o estudo da cinética de secagem permite a descrição do processo por meio de modelos matemáticos e obtenção de informações, que auxiliam na compreensão do fenômeno … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 22 publications
(16 reference statements)
0
3
0
1
Order By: Relevance
“…It can be considered an intermediate value, as the variation range is 12.7-110.0 kJ mol -1 for most food products (Zogzas et al, 1996). A lower activation energy corresponds to easy moisture removal from the material subjected to drying (Kosasih et al, 2020) because the activation energy is the energy barrier that must be overcome to start the mass diffusion from the wet material (Li et al, 2019;Xie et al, 2017), and variations are commonly found, as it can be influenced by the shape of the product, initial and final moisture content, chemical composition, structure, and the imposed drying conditions (Siqueira et al, 2020b).…”
Section: Resultsmentioning
confidence: 99%
“…It can be considered an intermediate value, as the variation range is 12.7-110.0 kJ mol -1 for most food products (Zogzas et al, 1996). A lower activation energy corresponds to easy moisture removal from the material subjected to drying (Kosasih et al, 2020) because the activation energy is the energy barrier that must be overcome to start the mass diffusion from the wet material (Li et al, 2019;Xie et al, 2017), and variations are commonly found, as it can be influenced by the shape of the product, initial and final moisture content, chemical composition, structure, and the imposed drying conditions (Siqueira et al, 2020b).…”
Section: Resultsmentioning
confidence: 99%
“…Figure 5a shows that there were the effective wavelengths obtained from the Vis‐NIR range (463–1000 nm) that corresponds to the O–H, C–H (third overtone of resins and polysaccharides), and N–H stretching (third overtone of amino acids) (Ru et al., 2019). Currently, there are few studies on detecting seed compound substance contents to certain seed conditions (Albishri et al., 2013; Köçeroğlu et al., 2020; Siqueira et al., 2020). To test the watermelon seeds’ condition, this study used different methods to select useful information.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, watermelon seeds with unknown storage conditions might result in the waste of financial, and natural resources and a reduction of watermelon products (De Vitis et al., 2020; Jin et al., 2022). It is also possible that native seeds are not always ready for usage straight away after their harvesting season and frequently require a storage period before delivery to practitioners (Siqueira et al., 2020). Hence, it is of the essence to ascertain the viability of watermelon seeds’ status to prevent the loss of farmers in their agricultural sectors.…”
Section: Introductionmentioning
confidence: 99%
“…No entanto, a secagem de produtos agrícolas é uma operação que demanda um alto consumo energético e por isso a influência da temperatura, cinética e velocidade do ar de secagem vem sendo alvo de estudos nos últimos anos (Alves et al, 2014;Taşeri et al 2018;Santos et al, 2020a;Santos et al, 2020b;Siqueira et al, 2020;Almeida et al, 2020;Rigueto et al, 2020). Partindo disso, a aplicação de uma fonte energética alternativa pode contribuir para redução de custo operacionais relacionados a secagem.…”
Section: Introductionunclassified